The long Mars : a novel - Pratchett, Terry (Pratchett, Terry. Long Earth series., 2014)
"The third novel in Terry Pratchett and Stephen Baxter's "Long Earth" series, which Io9 calls "a brilliant science fiction collaboration.""--